SCADA and distributed control system of a chemical products dispatch process - León Velarde, César Gerardo (2021)
The objective of this article is to show the application of a supervision, control and acquisition system of an industrial network of chemical products, for which the design of the control logic and the architecture of the industrial network on Profibus-DP protocols is described and Ethernet, with a peripheral terminal station ET-200, through the Siemens CP433 programmable logic controller and level sensor sensors, coupled to radar-type transmitters with an accuracy of ± 0.5 mm. As findings of the implementation of the control system, it was possible to demonstrate the optimal regulation of the filling system of the 3-compartment trucks with a capacity of 300 Kilos each, generating the elimination of spills of the chemical product, as well as the reduction of polluting particles in the work environment. Finally, as a direct consequence, the productivity of the company was improved, which is a relevant aspect at the level of planning, management and direction.